2012
DOI: 10.1111/tbed.12000
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Schmallenberg virus in differentCulicoidesspp. by real-time RT-PCR

Abstract: Summary:To identify possible vectors of Schmallenberg virus (SBV), we tested pools containing heads of biting midges (Culicoides) that were caught during the summer and early autumn of 2011 at several places in Belgium by real time RT-PCR. Pools of heads originating from following species: C. obsoletus complex, C. dewulfi and C. chiopterus were found positive, strongly indicating that these species are relevant vectors for SBV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
152
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(167 citation statements)
references
References 16 publications
10
152
0
5
Order By: Relevance
“…Culicoides obsoletus -a major species of interest for virus transmission in northern Europe (Carpenter et al, 2008;De Regge et al, 2012) -seems to have a wide host range, and is likely to be particularly interested in humans under field conditions. This species showed mammalophilic preferences (mainly for humans) in the field experiments -probably caused by greater emission of carbon dioxide -but ornithophilic and mammalophilic preferences (chicken and sheep) based on VOCs released from skin surfaces in the laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Culicoides obsoletus -a major species of interest for virus transmission in northern Europe (Carpenter et al, 2008;De Regge et al, 2012) -seems to have a wide host range, and is likely to be particularly interested in humans under field conditions. This species showed mammalophilic preferences (mainly for humans) in the field experiments -probably caused by greater emission of carbon dioxide -but ornithophilic and mammalophilic preferences (chicken and sheep) based on VOCs released from skin surfaces in the laboratory experiments.…”
Section: Discussionmentioning
confidence: 99%
“…Behavioural studies using olfactometers or wind or flight tunnels in which a specific number of biting insects are released are very rare (Bhasin et al, 2000b) due to the difficulty of obtaining a sufficient number of insects, given the complexity of maintaining many Culicoides species of interest under controlled conditions. Only a few speciesof limited interest in northern Europe -are commonly bred (Jones, 1964;Fahrner and Barthelmess, 1988;Kremer and Lienhart, 1998), and these do not include species of the subgenus Avaritia (particularly Culicoides obsoletus Meigen 1818), considered to be vectors of BTV and SBV (Mehlhorn et al, 2007;Carpenter et al, 2008;Hoffmann et al, 2009;De Regge et al, 2012;Elbers et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the available data give a first impression on land cover variables explaining the distribution of the German Culicoides fauna. Moreover, the German land cover data ATKIS ® were successfully used to develop species distribution models for thirteen Culicoides species, including C. chiopterus, C. dewulfi, and C. scoticus as potential vectors of the BTV (Meiswinkel et al, 2007;Dijkstra et al, 2008) and Schmallenberg virus (Meiswinkel et al, 2007;Dijkstra et al, 2008;De Regge et al, 2012;Rasmussen et al, 2012). Furthermore, our study showed that multi-scale modelling is a promising approach to model the distribution of Culicoides species.…”
Section: Discussionmentioning
confidence: 99%
“…Several species of the genus Culicoides (Diptera: Ceratopogonidae) are considered to be potential vectors of the bluetongue virus (BTV) (Meiswinkel et al, 2007;Dijkstra et al, 2008) Culicoides species as capable vectors (Beer et al, 2013), as these are also here considered to be the main vectors (De Regge et al, 2012;Rasmussen et al, 2012). Although there is huge lack of knowledge about the causal connection between environmental variables and the distribution of biting midges, several studies modelled biting midge distribution and phenology using different sets of environmental data (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…The disease was rapidly spread to several European countries by midges of the genus Culicoides as C. dewulfi, C. chiopterus (de Regge et al 2012) and C. obsoletus. It has been demonstrated that the virus can replicate in the latter (Montgomery, Tack & Obonyo 2012).…”
Section: Introductionmentioning
confidence: 99%